Aplicación de abonos orgánicos en la col brassica oleracea en el cantón Balao - Payes Alejandro, Enrique Iván (2010)
The present research abont application of organic fertilizer in the cabbage (Brassica oleracea) in the Balao Cantón, it was made at the Colegio Fiscal Técnico Balao, which is located to a 1 km of the main place in the Guayas province. The objectives of the research were: 1. to establish the reaction of the cabbage to organic fertilizers, 2.to determine the treatment of better yield, and 3. to realize the economic analysis of the treatments. It was used seeds of cabbage variety flat duch to continuous jet and covering them with crumbled soil. The soil were supplied water until to get the capacity of the soil, when the germination was produced, the irrigation was made with a frequency of each two days. The trasplante was 27 days and when the plant presented five true leaves. The fertilizers were applied in the 21, 36, and 51 days in each treatment, what was the Each treatment was distributed at random Blkocks with four treatments and a proof making five repetitions. In the analysis of variety there wasn’t significant for the treatment in the variable of high of the plant in the 30, 60 and 90 days. In the formation of cabbages the results weren´t important. In the presence of pests and diseases there wasn´t importance of anyone of them. In the numbers of cabbages at he harvest, the results were significant at the 5% of the probabilities. In the diameter of the cabbage, the humus of worm resulted to be different to other treatments and in the yield the Eco- humus was the best of all.